PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS II SD NEGERI 77 PEKANBARU - Syarifah Nuraini; Jesi Alexander Alim; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of the problem in this research is based on the low level of the results of learning math grade II SD Negeri 77 Pekanbaru, caused by a teacher teaching focused on books, students who are less interested learning materials and a lack of innovation in the learning process. The action taken is the implementation of Direct Learning Model. This research aims to improve the results of learning math grade II in SD Negeri 77 Pekanbaru year 2014/2015. Design research is Research Action class (PTK). The research was conducted in two cycles with four (4) stages of cycle. Data collection instruments used, namely the observation sheets teachers and students as well as test results of learning. After the applied learning models direct then the results of the study showed that application of the model of direct learning can improve the results of learning math grade II SD Negeri 77 PekanbaruKeywords: Direct Learning, Student Achieevement The Result of Mathematics Studies